CIGARETTE SMOKING AND DIABETIC PERIPHERAL NEUROPATHY : A SYSTEMATIC REVIEW - Derrick; Halim, Hendry (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2022)
It is common knowledge that smoking cigarettes is associated with a wide range of detrimental effects on one's health, including the development of a number of diseases and conditions that can manifest in any organ or system of the body. Diabetes can lead to a wide variety of microvascular problems, some of which include ulcers and amputations, dysfunctions in erectile function and autonomic function, and erectile dysfunction. DPN, or diabetic peripheral neuropathy, is a microvascular complication of diabetes that is part of a larger spectrum of diabetic problems. It is also known as distal symmetrical polyneuropathy or sensorimotor neuropathy. The most common of these problems is diabetes peripheral neuropathy (DPN), which affects approximately 30 percent of persons who have diabetes types. It is largely agreed upon that oxidative stress is the final mechanism that is accountable for the cellular damage seen in diabetic neuropathy. [Citation needed] [Citation needed] It is defined by high levels of persistent generation of reactive oxygen species (ROS), which can include ozone, superoxide, hydrogen peroxide, singlet oxygen, and organic peroxides in cells. ROS can also be produced when cells are exposed to persistently high quantities of singlet oxygen. The term "peroxidative stress" can also be used to refer to this condition. Although there is inconsistency in the relationship between diabetic peripheral neuropathy and smoking cigarettes, research that reveal an association between the two show that the prevalence of the condition is greater than 10%.